(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2009)
Key words: Vigna; Interspecific crosses; Prezygotic incompatibility Bangladesh j. genet. biotechnol. 7(1&2): 15-17 2006 (June & December)